The effect of iron and bismuth addition on the microstructural, mechanical, and thermal properties of Sn–1Ag–0.5Cu solder alloy. Issue 9 (August 2015) - Mahdavifard, M.H.; Sabri, M.F.M.; Shnawah, D.A.; Said, S.M.; Badruddin, I.A.; Rozali, S.
Abstract: This work investigates the effect of Fe and Bi addition, 0.05 wt.% Fe and 1 wt.% or 2 wt.% Bi, on the microstructural, mechanical, and thermal properties of the low silver Sn–1Ag–0.5Cu (SAC105) solder alloy. Adding Bi and Fe to SAC105 increased ultimate tensile strength (UTS) and yield strength and decreased the total elongation which is related to solid-solution and precipitation strengthening effects by Bi in the Sn-rich phase. While 0.05 wt.% Fe made few FeSn2 in the solder bulk which does not have considerable effect on mechanical properties. Scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX) showed that Bi strengthen solder by scattering in the bulk of SAC105-Fe solder alloy, thereby increased β-Sn and degenerated Cu6 Sn5 and Ag3 Sn into a chain-like arrangement. Surface fracture of SAC–Fe–Bi solder alloys showed brittle fracture because Bi prevented β-Sn to deform and therefore Bi decreased its ductility. Finally, Bi significantly reduces the melting point and undercooling.